Preparation of Biopesticide Powder from Jicama (Pachyrhizus erosus) Leaf Extract to Eradicate Whitefly Pests (Bemisia tabaci G.) on Eggplant Plants (Solanum melongena L.) - Laila Silvy Fatmawati; Natasya Dian Andini; Dr. Margono (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2023)
The use of synthetic pesticides in Indonesia is increasingly widespread because they are considered effective in killing pests. However, synthetic pesticides leave residues that can cause environmental pollution and human health problems. Therefore, another alternative is needed, namely switching to using environmentally friendly vegetable pesticides. One of the alternatives is biopesticide powder from jicama leaf extract as a whitefly pest controller. Pomace leaves contain active compounds that are toxic to whitefly, namely rotenone which is a group of flavonoid compounds. The method of making this biopesticide powder consists of 2 stages, the first is the preparation of jicama leaf extract through a maceration process for 2 days with the ratio of leaf powder and solvent, namely 40 g, 60 g, 80, and 100 g of jicama leaf powder in 500 ml of 96% ethanol. The second stage is the processing of jicama leaf extract into biopesticide powder through the encapsulation process, namely mixing the extract with maltodextrin using a weight ratio of extract maltodextrin, namely 1 : 2 (w : w). The analysis carried out was the test of biopesticide effectiveness against whitefly. After testing, it was found that the biopesticide powder that was effective in eradicating whitefly pests was a biopesticide powder with a ratio of 100 grams of jicama leaf powder in 500 mL of 96% ethanol with a dissolution dose of 20 g/L in water, which was able to kill whitefly with a mortality percentage of 100% on day 3.